Maternal and pregnancy outcomes following PMTCT cohort registration in a displaced setting - A retrospective study. (2024)
BACKGROUND/AIM: This study assessed maternal and pregnancy outcomes following the Prevention of Mother-to-Child Transmission (PMTCT) cohort registration in a displaced setting. RESULTS: Of the 223 HIV-positive pregnant women, 201 were enrolled in the program. However, only 186 maternal records met the inclusion criteria. Registration for the PMTCT program occurred primarily during the prenatal period, between the ages of 26 and 30, with a mean gestational age of 15.2 weeks. Only 5.95 reported facility delivery, and up to 70% had over 4 PMTCT follow-up visits before delivery (χ2 = 6.825, P = 0.03). The retention rate among the cohort was 98.4%, with 62 % of the women being active throughout the program and over 86% having a live birth. Most miscarriages occurred during the first trimester. Bivariate analysis suggested that aside from maternal age, similar factors affected maternal and pregnancy outcomes. These factors include maternal prior PMTCT experience, total number of visits, and the place of delivery. CONCLUSIONS: Active follow-up and documentation constitute an effective strategy to improve PMTCT maternal retention in care and improve patient outcomes. Ensuring that women are active in PMTCT care by engaging community health workers in service delivery will create positive outcomes in the program.